Posted by **Emily** on Thursday, August 22, 2013 at 4:16pm.

1) evaluate without a calculator: a)sin(3.14/4) b) cos(-3(3.14)/4) c) tan(4(3.14)/3) d) arccos(- square root of three/2) e) csctheata=2

2) verify the following identities: a) cotxcosx+sinx=cscx b)[(1+sinx)/ cosx] + [cosx/ (1+sinx)]= 2secx c) (sin^2x + 2sinx+1)/cos^2x= (1+sinx)/(1-sinx)

- Math -
**Reiny**, Thursday, August 22, 2013 at 5:25pm
You should memorize the following diagrams:

1. the 30°-60°-90° triangle with matching sides

1 -- √3 -- 2 (angles in radians, π/6 π/3 π/2)

2. the 45° -- 45° -- 90° triangle with corresponding sides 1 -- 1 -- √2

So sin π/4 or sin 45° = 1/√2

arccos(-√3/2) = .....

I know from looking at my triangle that cos60° or cosπ/3 = √3/2

Also I know that the cosine is negative in II and III

so arccos(-√3/2) = 180-60 = 120° or 2π/3

cscØ = 2

sinØ = 1/2

Ø = 30° or π/6 , looking at my triangle

With identities, it is usually a good idea to change all trig ratios to sines and cosines, and let the chips fall as they may.

I will do the first one:

LS = cotx cosx + sinx

= (cosx/sinx)(cosx) + sinx

= (cos^2 x + sin^2 x)/sinx

= 1/sinx

= csc x

= RS

try the others using that concept, let me know if you were successful.

## Answer this Question

## Related Questions

- Precalculus/Trig - I can't seem to prove these trig identities and would really ...
- Trigonometry - Prove the following trigonometric identities. please give a ...
- Trigonometry. - ( tanx/1-cotx )+ (cotx/1-tanx)= (1+secxcscx) Good one! ...
- Trig........ - I need to prove that the following is true. Thanks (cosx / 1-sinx...
- trig - express this in sinx (1/ cscx + cotx )+ (1/cscx- cotx) i got 2sinx is ...
- Math (trigonometric identities) - I was given 21 questions for homework and I ...
- Math - Verify the identity . (cscX-cotX)^2=1-cosX/1+cosX _______ sorry i cant ...
- Calculus 2 Trigonometric Substitution - I'm working this problem: ∫ [1-tan...
- Math - Im really struggling with these proving identities problems can somebody ...
- Math 12 - Simplify #1: cscx(sin^2x+cos^2xtanx)/sinx+cosx = cscx((1)tanx)/sinx+...